2019
DOI: 10.1101/757542
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking infection dynamics at single-cell level reveals highly resolved expression programs of a large virus infecting algal blooms

Abstract: 27Nucleocytoplasmic large DNA viruses have the largest genomes among all viruses and 28 infect diverse eukaryotes across various ecosystems, but their expression regulation and 29 infection strategies are not well understood. We profiled single-cell transcriptomes of the 30 worldwide-distributed microalga Emiliania huxleyi and its specific coccolithovirus 31 responsible for massive bloom demise. Heterogeneity in viral transcript levels detected among 32 single cells was used to reconstruct the viral transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…With the increased use of state-of-the-art single-cell and single-virus genomics approaches in virus ecology, use of single-cell viral infection-dynamics visualisation methods, and efforts to link mechanistic understanding from laboratory experiments to larger scale field observations of hostvirus interactions (Allers et al, 2013;Ku et al, 2020;Nissimov et al, 2019), it is likely that the number of studies using virus isolates from private collections (Table 1) will increase. At the same time, the microbiology field in general is also recognising that many studies across the different sub-disciplines can benefit from standardisation of protocols and common analytical frameworks (Thompson et al, 2017), improving the reproducibility of studies, and the way key findings are being reported.…”
Section: An Aquatic Virus Culture Collection Will Allow For Increasedmentioning
confidence: 99%
“…With the increased use of state-of-the-art single-cell and single-virus genomics approaches in virus ecology, use of single-cell viral infection-dynamics visualisation methods, and efforts to link mechanistic understanding from laboratory experiments to larger scale field observations of hostvirus interactions (Allers et al, 2013;Ku et al, 2020;Nissimov et al, 2019), it is likely that the number of studies using virus isolates from private collections (Table 1) will increase. At the same time, the microbiology field in general is also recognising that many studies across the different sub-disciplines can benefit from standardisation of protocols and common analytical frameworks (Thompson et al, 2017), improving the reproducibility of studies, and the way key findings are being reported.…”
Section: An Aquatic Virus Culture Collection Will Allow For Increasedmentioning
confidence: 99%
“…HHQ has been shown to modulate EhV infection dynamics; however, protection from viral induced mortality must coincide with exposure to the QS signal early [< 24 h post infection (hpi)] in infection and requires remodeling of host physiology (Pollara et al, 2021;Harvey et al, 2023). Moreover, this early window in EhV infection (within 8 hpi) corresponds to the time when EhV hijacks the host's replication machinery to fuel viral gene synthesis involved in DNA replication, nucleotide metabolism, and lipid biosynthesis in parallel with repression of host nuclear and organelle-encoded genes (Ku et al, 2020). Moreover, within 24 h of HHQ exposure, E. huxleyi cells undergo metabolic and transcriptional changes leading to halted DNA replication, an increase in DNA lesions, and the upregulation of the DNA damage response with a notable lack of both DNA repair and apoptosis (Pollara et al, 2021).…”
Section: Introductionmentioning
confidence: 99%